Features of ICU-hospitalised patients suffering from SARS-CoV-2 and swallowing disorder: a systematic review - Rosales Lillo, Felipe; Cabezas Godoy, Catalina Belén; Figueroa Sobrino, Camila Fernanda; Hevia Acuña, Stephanie Alexandra; Skinner Palma, Constanza Beatriz (Revista de Investigación en Logopedia, 2022)
The purpose of this study is to determine the features of ICU-hospitalised patients suffering from SARS-CoV-2 and swallowing disorder between 2020 and 2021. For that goal a systematic review was performed. PubMed, ScienceDirect, Web of Science and Scielo were used to find the interest articles. The inclusion criteria were articles in English, Spanish and Portuguese published from 2020, with patients over 18 years old hospitalised in Intensive Care Units, and diagnosed with COVID-19 and dysphagia. The results show that the mean stay of the hospitalisation in patients with SARS-CoV-2 in Intensive Care Units varies between 15 and 34 days. In relation to the artificial airway, both orotraqueal intubation and tracheostomy are frequents. For orotraqueal intubation, its use varies between a minimum mean of 10 days and a maximum mean of 17 days. For tracheostomy, its use fluctuates between a minimum and maximum mean of 19 and 30 days respectively. Oropharyngeal dysphagia is frequent in these patients. In patients suffering from COVID-19 and dysphagia, the mean of days of hospitalisation and the mean of days using an artificial airway are higher than the reported during non-pandemic times. The longer the use of an artificial airway, the greater the risks of dysphagia and hospital stay in Intensive Care Units. Oropharyngeal dysphagia is frequent in patients with SARS-CoV-2. It is recommended to perform extra observational and experimental research in the area.